2000
DOI: 10.1054/bjoc.2000.1261
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 from prostate cancer cells is enhanced by bone contact which blocks osteoclastic bone resorption

Abstract: The causes for the propensity of metastasized prostate cancer cells to grow in bone and to induce osteoblastic lesions remain unresolved. Co-culture of human prostate cancer cell lines with bone slices was determined to increase the level of endothelin-1 (ET-1) mRNA and its production. ET-1 is an ejaculate protein that also stimulates osteoblasts. Osteoclastic bone resorption was significantly blocked by the presence of androgen-independent prostate cancer cells in a dose-dependent manner as that of synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(62 citation statements)
references
References 20 publications
3
57
0
2
Order By: Relevance
“…In addition, growth factors synthesized by the increased numbers of osteoblasts become sequestered in the newly synthesized bone matrix and also become rich in the local microenvironment which promotes further tumor growth and survival. The osteoblastic nature of the metastases is further supported by inhibition of osteoclastic bone resorption by ET-1 [73].…”
Section: Microenvironment Of Bone Metastasesmentioning
confidence: 89%
“…In addition, growth factors synthesized by the increased numbers of osteoblasts become sequestered in the newly synthesized bone matrix and also become rich in the local microenvironment which promotes further tumor growth and survival. The osteoblastic nature of the metastases is further supported by inhibition of osteoclastic bone resorption by ET-1 [73].…”
Section: Microenvironment Of Bone Metastasesmentioning
confidence: 89%
“…Indeed exogenous ET-1 increases prostate cancer cell proliferation and enhances the mitogenic effect of other growth factors including, IGF-1, PDGF and EGF [33]. The bone microenvironment may enhance ET-1 expression by cancer cells [34]. One mechanistic definition of ET-1 action includes the finding that ET-1 drives net bone formation by inhibiting osteoclast bone resorption and osteoclast motility [35].…”
Section: Osteoblastic Bone Metastasismentioning
confidence: 99%
“…PECs produce ET-1, and its receptor, ETa, is present throughout the prostate gland [73][74][75]. ET-1 is also produced by PCa cells in a bone environment [76]. Experiments using an osteoblast mouse model [72] showed that tumours producing ET-1 (e.g., PCa) act via ETa receptors on osteoblasts to stimulate accelerated bone formation.…”
Section: Molecular Mechanisms Of Metastatic Prostate Cancer In the Bomentioning
confidence: 99%